Ular Tangga Numerasi: Inovasi Media Pembelajaran Matematika untuk Siswa Sekolah Dasar - Yustitia, Via; Rakhmah, Yasmine Nur Izzah; Astuti, Indra Puji; Untari, Erny (Universitas Nusantara PGRI Kediri, 2024)
The low numeracy skills of students are caused by a lack of practice, the results of literature studies and interviews with class V teachers at SDN Sugihrejo 1 show that students' AKM numeracy scores are low. So, researchers are interested in creating numeracy snakes and ladders learning media for fifth grade elementary school students. The research objectives are: 1) describe the process of developing Snakes and Ladders Numeracy Learning Media for fifth grade elementary school students; 2) describe the feasibility of the Snakes and Ladders Numeracy Learning Media product for fifth grade elementary school students. This type of R&D (Research and Development) research uses a 4D model which is only carried out up to three stages of development, namely, 1) definition; 2) planning (design); and 3) development. This research resulted in 1) a development process that produced numeracy snakes and ladders learning media for fifth grade elementary school students; 2) the assessment results from 3 expert validators regarding media assessment are in the